T-lymphocyte profiles differ between keratoacanthomas and invasive squamous cell carcinomas of the human skin - Bauer, Corinne; Abdul Pari, Ashik Ahmed; Umansky, Viktor; Utikal, Jochen; Boukamp, Petra; Augustin, Hellmut; Goerdt, Sergij; Géraud, Cyrill; Felcht, Moritz (Cancer immunology immunotherapy, 2018)
Background: T-lymphocytes are involved in tumor progression and regression. Actinic keratoses (AK) are atypical proliferations of keratinocytes of the skin. Some AK progress into invasive cutaneous squamous cell carcinomas (cSCC). Keratoacanthomas (KA) are either classified as a cSCC subtype or a benign tumor with histologic resemblance to well-differentiated cSCC as it is supposed to regress spontaneously. In contrast, cSCC represent malignant tumors that may metastasize. Objectives: To compare the T-lymphocyte profiles of AK, KA and cSCC in relation to PD-L1 expression. Methods: Tissue micro-arrays of 103 cases of AK, 43 cases of KA and 106 cases of cSCC were stained by immunohistochemistry for E-cadherin, CD3, CD4, CD8, FOXp3, and the receptor–ligand pair PD-1/PD-L1. Immunohistological scores were computationally determined to assess PD-L1 expression as well as the expression profiles of T-lymphocytes. Results: AK had lower numbers of CD3+ and PD-1+ cells compared to KA and lower numbers of CD3+, CD8+ and PD-1+ cells in comparison with cSCC. KA showed significantly higher numbers of CD4+ and FOXp3+ cells as well as lower numbers of CD8+ cells in comparison with invasive cSCC. cSCC expressed significantly more PD-L1 in comparison with AK and KA. Among cSCC PD-L1 expression was higher in moderately and poorly-differentiated cSCC than in well-differentiated cSCC. Increased PD-L1 expression also correlated with increased numbers of CD4+, CD8+ and FOXp3+ cells in cSCC. Conclusions: Tumor-associated T-lymphocyte infiltrates showed significant differences between AK, KA and invasive cSCC. PD-L1 expression correlated with invasion of T-cell infiltrates in invasive cSCC.
Gesehen am 05.03.2020